2015
DOI: 10.1111/jeb.12575
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of complex life cycles in trophically transmitted helminths. I. Host incorporation and trophic ascent

Abstract: Links between parasites and food webs are evolutionarily ancient but dynamic: life history theory provides insights into helminth complex life cycle origins. Most adult helminths benefit by sexual reproduction in vertebrates, often high up food chains, but direct infection is commonly constrained by a trophic vacuum between free-living propagules and definitive hosts. Intermediate hosts fill this vacuum, facilitating transmission to definitive hosts. The central question concerns why sexual reproduction, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 146 publications
(240 reference statements)
2
38
0
Order By: Relevance
“…Mathematical models have revealed that increases in life-cycle complexity that enhance the probability of transmission to the definitive host, opportunities for sexual outcrossing in that host, or lifetime fecundity should be under strong selection in many plausible situations (Brown et al, 2001;Choisy et al, 2003;Parker et al, 2003Parker et al, , 2015. Predictions from these models generally fit well with empirical observations.…”
Section: Introductionmentioning
confidence: 78%
“…Mathematical models have revealed that increases in life-cycle complexity that enhance the probability of transmission to the definitive host, opportunities for sexual outcrossing in that host, or lifetime fecundity should be under strong selection in many plausible situations (Brown et al, 2001;Choisy et al, 2003;Parker et al, 2003Parker et al, , 2015. Predictions from these models generally fit well with empirical observations.…”
Section: Introductionmentioning
confidence: 78%
“…Prey of the original host may frequently have ingested parasite transmission stages because of their proximity to the original host and thereby may have become intermediate hosts. Being prey to the original host may enhance transmission back to that host [106]. Such downward incorporation has been associated with the occurrence of a ‘trophic vacuum’, i.e.…”
Section: Evolutionary Pathways In Transmission Modementioning
confidence: 99%
“…Platyhelminthes appear to present such an example of downward incorporation: the lineage ancestral to digeneans and cestodes has become parasitic in invertebrates [101]. Paratenic hosts may also be acquired by downward incorporation as a means of increasing transmission [106]. Intermediate hosts could also be added via ‘lateral incorporation’ if the parasite has multiple hosts involved; in a generalist pathogen each of two parasite stages come to specialize on one of the hosts [106].…”
Section: Evolutionary Pathways In Transmission Modementioning
confidence: 99%
See 1 more Smart Citation
“…In a way, the present-day conditions of parasites' transmission in the high Arctic are comparable with those in the glacial refugia. The instances of non-specific parasitism can be considered as a model demonstrating different stages of lateral incorporation (sensu Parker et al, 2015) of new hosts, which may result in speciation of helminths.…”
Section: Helminth Abundance and Host Colonizationmentioning
confidence: 99%